Building and Evaluating a Distributional Memory for Croatian - Šnajder, Jan; Padó, Sebastian; Agić, Željko (2013)
We report on the first structured distributional semantic model for Croatian, dm.hr. It is constructed after the model of the English Distributional Memory (Baroni and Lenci, 2010), from a dependency-parsed Croatian web corpus, and covers about 2M lemmas. We give details on the linguistic processing and the design principles. An evaluation shows state-of-the-art performance on a semantic similarity task with particularly good performance on nouns. The resource is freely available.
ENG